Standardization of Tragopogon graminifolius DC. Extract Based on Phenolic Compounds and Antioxidant Activity - Mohammad Hosein Farzaei; Mahnaz Khanavi; Ghazaleh Moghaddam; Farzaneh Dolatshahi; Roja Rahimi; Mohammad Reza Shams-Ardekani; Gholamreza Amin; Mannan Hajimahmoodi (Journal of Chemistry)
Tragopogon graminifolius DC. (TG), Compositae family, is traditionally used for the treatment of various diseases like gastrointestinal and hepatic disorders. The aim of the present study is to standardize extracts from TG used for preparation of different dosage forms in traditional Iranian medicine (TIM) based on phenolic compounds. For this purpose, total phenolic content and some phenolic compounds were determined in ethanolic extracts from aerial part and root of TG by HPLC method. Furthermore, antioxidant activity was evaluated using DPPH-HPLC methods. Caffeic acid, gallic acid, ρ-coumaric acid, ferulic acid, and catechin were detected in root and aerial part of TG. ρ-Coumaric acid (6.357 ± 0.014 mg·g−1) was dominant phenolic compound in aerial part followed by ferulic acid (1.24 ± 0.018 mg·g−1). Also, ρ-coumaric acid (2.685 ± 0.031 mg·g−1) was highly abundant in root, followed by catechin (2.067 ± 0.021 mg·g−1). Antioxidant activity of root extract (460.45 ± 0.78 µg Vit.E.E·mL−1) was better than that of aerial part. Generally, phenolic compounds are one of the major constituents of TG and could be used as markers for standardization of dosage forms prepared from this plant. Also, TG demonstrated significant antioxidant activity using DPPH-HPLC method. Phenolic compounds of TG may be responsible for its marked antioxidant properties.